Acetosolv pulping modeling of oil palm frond fibers - Nasrullah RCL; I. Mazlan (Syiah Kuala University, 2011)
Oil palm frond fibers were pulped using acetosolv pulping in laboratory scale batch digester. A central composite desigh was used to investigate the process and to study the effect of its variables on pulp quality and yield. A second order polynomial regression model, using three in dependent process variables, was found to be appropriate for describing acetosolv pulping oil palm fibers. The overall pulping conditions, which maximize yield while subject to a restriction of kappa number 19.93 were estimated at pulping time of 130 mins, a pulping temperature of 153 oC, AcOH of 85 % and HCl of 0.25 %